SESN2 ablation weakens exercise benefits on resilience of gut microbiota following high-fat diet consumption in mice - Chunxia Yu; Peng Zhang; Sujuan Liu; Yanmei Niu; Li Fu (Food Science and Human Wellness)
Gut dysbiosis is associated with several pathological processes. Previous study showed that regular exercise can protect against dysmetabolism in high-fat diet (HFD) fed mice through butyrate-SESN2 pathway, and SESN2 ablation weakened the protective effects of exercise. Here, we investigated whether SESN2-deficiency suppresses the exercise response to microbiota composition and subsequently reduces the benefits of exercise on dysmetabolism induced by HFD. Wild type (WT) and SESN2−/− mice were assigned to five-groups, fed with either normal chow or HFD and with or without exercise training for 15-week. Fecal microbiota composition and function were assessed by 16S rRNA sequencing. The sequencing results showed that SESN2−/− mice displayed differed microbiome profile from WT mice. Exercise enriched the microflora diversity and increased the beneficial microbial species in WT mice, and SESN2 ablation weakened the beneficial effects of exercise on microbial resilience following HFD consumption. Moreover, network analysis revealed that exercise increased correlation density and clustering of operational taxonomic units in WT mice only. KEGG demonstrated that some dominant metabolism-related enzymes and modules increased in SESN2−/− mice. Our results indicated that the effects of exercise on metabolism are associated with the perturbations of gut microbiota composition and function, suggesting that SESN2 contributes to maintain metabolic homeostasis.−